Tree triangular coding image compression algorithms - Shukla K.K.; Prasad M.V. (My University, 2025)
This chapter presents four new image compression algorithms namely, Three-triangle decomposition scheme, Six-triangle decomposition scheme, Nine-triangle decomposition scheme and the Delaunay Triangulation Scheme. Performance of these algorithms is evaluated using standard test images. The asymptotic time complexity of Three-, Six-, and Nine-triangle decomposition algorithms is the same: O(nlogn) for coding and θ(n), for decoding. The time complexity of the Delaunay triangulation algorithm is O(n 2 logn) for coding and O(nlogn) for decoding, where n is the number of pixels in the image. © K. K. Shukla 2011.